Beyond truth-telling: A replication study on school choice - Tommy Andersson; Dany Kessel; Nils Lager; Elisabet Olme; Simon Reese (Lund University, School of Economics and Management, Department of Economics, 2024)
4207 In a recent paper, Fack et al. (2019, American Economic Review) convincingly argue and theoretically demonstrate that there may be strong incentives for students to play non-truth-telling strategies when reporting preferences over schools, even when the celebrated deferred acceptance algorithm is employed. Their statistical test also rejects the (weak) truth-telling assumption in favour of another assumption, called stability, using a single data set on school choice in Paris. This paper uses Swedish school choice data and replicates their empirical finding in 52 of the 58 investigated data sets (P-value threshold 0.05).
Keywords: D12; D82; I23; 330; school choice; deferred acceptance algorithm; truth-telling; stability; replication study